Changing Patterns of Thyroid Pathology and Trends of Surgical Treatment - Sulaiman, Tharwat I.; Al-Sarraf, Salim A.; Al-Rrawak, Khudayer (Journal of the Faculty of Medicine Baghdad, 2009)
Background: There were definite changes in pathologies involving thyroid gland allover the world with increasing incidence of thyrotoxicosis and differentiated malignancies. Patients and methods: 224 patients were operated upon by the same surgeon during 15 years period. Those patients were divided into two groups (GI from June 1990 up to June 2000) and (GII from June 2000-June 2005). Results: female to male ratio was 3.3:1. The most common presentation among both groups was Multinodular goiter (MNG) 76.8%. toxic goiter was recorded in 24% of patient with increase among GII patients. A significant effect of stress on the increasing incidence of thyrotoxicosis was elicited in more than 50% of patients with thyrotoxicosis. Malignant thyroid tumors constituted 8.5% of the diseases and they were mostly papillary carcinoma. There was increase incidence of malignant thyroid tumors among GII patients (2.65% in GI versus 13.5% in GII). The trend toward more radical surgery was evident among GII patients Conclusion: thyroid malignancy and thyrotoxicosis are increasing in our country and stress factor might play a role in this rise. Due to the previous changes, the surgeon attitude had changed toward more radical surgery.